COMMUNITY EDUCATION IN THE DEVELOPMENT OF THE COMMUNITY - Jajat S. Ardiwinata; Dinno Mulyono (IKIP Siliwangi Bandung, 2018)
Community education is a sustainable process in the community, built with awareness and sustained participation, in an effort to build a new understanding and concept to improve the quality of life of the community itself. Community education is now moving back into building and developing societies with the same approach as the hundreds and centuries-old approach to the prosperity of society. With the right theoretical framework, the right approach and the right program implementation models, community education can grow and develop into a power in education to build a better Indonesian society. Critical pedagogical theory and so forth is the main foundation in the development of concepts and subsequent thoughts related to public education.